Quality Improvement in Clinical Laboratories - Mohammed Ali Ahmed Albeshir; Faisal Saleh Matooq Aljasim; Jaffar Radi Ali Alatiyah; Mohammed Abdullah A Al Musilim; Yasir Salman Ahmed Althani; Mohammed Abdullah Essa Abu.Homed; Ali Matooq Abdullah Al Najjad; Jassim Ali Hussain Al-Jubarah; Mohammed Yasin Ali Al-Thani; May Yaseen Abdallh Al'humuod; Naji Hussain Saleh Alhassan; Nabeel Salman Mohamad Al Saleh (International Journal of Scientific Research and Innovative Studies, 2022)
Clinical laboratories play a critical role in healthcare delivery, providing vital diagnostic information for patient management. Ensuring the quality of laboratory testing is paramount to achieve accurate and reliable results, which directly impact patient care and outcomes. This review article explores the current strategies and advancements in quality improvement within clinical laboratories, highlighting the key areas of focus and future directions. Key words; Quality improvements, health providers , laboratory